Online borrowing system - Teh, Lee Na (Universiti Malaysia Sarawak, UNIMAS, 2006)
Digital storage of records is increasingly common nowadays. Therefore, the evolution from paper-based to paper-less is becoming usual. Hence, in order to replace the traditional way of managing record into an electronic and digital form, an ONLINE BORROWING SYSTEM (OBS) is introduced and delivered. It is said to be very helpful to reduce the complexity of tasks and provide a faster way in keeping and managing records. It helps to produce more systematic record management method. This report described how the system is analyzed, designed, implemented and tested.